Attachment in Psychotherapy: A Behavioral Approach and Clinical Implications - Rebeca Pardo-Cebrián; Gladis-Lee Pereira; Natalia Andrés-López; Amanda Muñoz-Martínez (Behavior and Social Issues, 2026)
Abstract Attachment theory, rooted in psychoanalytic and ethological theories, is one of the most influential models in psychology for understanding relational patterns. Originally developed to explain infant–caregiver bonding within developmental psychology, its application has expanded to clinical contexts as a model of relational intimacy. The assumption that early caregiving experiences shape adult relational functioning has further extended its influence within psychotherapy. However, attachment theory has been criticized for conceptual ambiguity, tautological explanations, methodological limitations, and potential gender and cultural biases. This narrative conceptual review integrates literature from attachment theory, behavior analysis, and cultural and feminist perspectives to examine the explanatory and clinical utility of attachment constructs. Behavior-analytic approaches have reframed attachment-related phenomena in functional terms, though cultural and contextual variables have received comparatively less attention. In response, this article proposes a functional reconceptualization of attachment as a behavioral pattern shaped by verbal, social, and cultural contingencies influencing relational learning histories and intimate repertoires. This perspective aims to improve the conceptual precision and clinical applicability of attachment-related constructs.